Uji Fitokimia dan Aktivitas Antioksidan Teh Daun Daruju (Acanthus illicifolius) - Shinta Ayu Nuryani; Shanti Dwita Lestari; Ace Baehaki (Universitas Sriwijaya, 2018)
The purposes of the research were to compare the method of makes daruju (Acanthus illicifolius) leaves the tea to determine the bioactive compounds. The research was conducted from June 2016 until December 2016. This research uses laboratory experimental methods and data analysis was done descriptively. The parameters observed testing phytochemical compounds flavonoids, alkaloids, tannins, saponins, phenols and steroids and analysis of antioxidant with DPPH and reducing power. The result showed that the crude extract daruju leaves tea has a bioactive compound acts as an antioxidant compound. The result of antioxidant activity DPPH methods was medium in the methanol extract with IC50 values of 101.4 ppm and boiled extract (217.5 ppm) and a very weak activity in the brewed extract (294.9 ppm) while the reducing power method shown good results in the methanol extract instead of boiled extract and brewed extract. From the results of the antioxidant activity of these three methods, the use of extraction are best is methanol. While the comparing from the method of makes daruju leaves the are best is boiled extract than brewed extract.